Does education mitigate terrorism?: Examining the effects of educated youth cohorts on domestic terror in Africa - Danzell, Orlandrew E. (Terrorism and political violence, 2020)
Policymakers often tout expanded access to education as an antidote for terrorism in Africa. Targeted economic development is also considered a necessary complement to education gains because young, well-educated individuals who lack viable opportunities are vulnerable targets of radicalization. Despite common assertions that poor socioeconomic circumstances drive radicalization, empirical research has hitherto neglected critical inquiry of these policies. Varied findings across cross-national studies of education expansion and the effects of burgeoning youth cohorts warrant a focused examination of regions plagued by the proliferation of extremist groups. This study explores the role of education in mitigating a turn to terror among youth in Africa by examining 50 countries from 1970 to 2011. Expansions in primary, secondary, and tertiary education appear to have different influences on domestic terrorism. In the sub-Saharan region, one model shows primary and secondary education reduced terrorism while others indicate non-monotonic effects in societies experiencing a youth bulge. These nuanced findings suggest education should not be relied upon to counter extremism without additional initiatives to facilitate socioeconomic opportunities. The implication of this paper’s findings are important for academics and policymakers eager to create stable polities across the African continent.